Why did Czech Banks Switch From Loans in 1995? - Jeffrey H. Nilsen (Swiss National Bank, Study Center Gerzensee, 1998)
The Czech banking system is seen by many observers to be the most successful of all former socialist economies'. But have Czech banks successfully provided worthy enterprises with sufficient credit from the funds made available to them? Using data from the Czech National Bank and data on individual Czech banks, I find evidence that in 1995 banks are provided with more deposits, but do not transform them into enterprise loans. I investigate the possible causes of this great portfolio switch and find that the central bank instituted a monetary tightening during a regime of fixed exchange rates and mobile capital. The central bank sterilized the continuing capital inflows. The resulting higher interbank interest rates and competition from foreign funds made the loan interest margin too narrow for Czech banks to profitably lend. The tight money strategy likely contributed to the bank failures in the following year and may have lead to greater concentration in the Czech banking system.
Keywords: E58; P34; 330; Banking; Capital Flows; Capital Mobility; Central Banking; Economy in Transition; Fixed Exchange Rates; Monetary Policy; Bank; Kreditpolitik; Kreditgeschäft; Tschechien